FROM THE GUIDE TO NONEXISTENT BIRDS: AN ORNITHOLOGICAL LOGIC. - DUVVOORI, KAVI (Michigan Quarterly Review)
The article focuses on The Guide to Nonexistent Birds , a computational literary experiment that uses logic programming to generate poetic descriptions of imaginary birds while reflecting on the history and philosophy of artificial intelligence. Topics include the creative fusion of code and literature through Prolog-based generative writing, the ethical and historical critique of early AI paradigms, and the exploration of how logic, language, and technology shape human understanding.